Assessment of Contract Change Orders and Their Impact on Contractor Performance in Construction Projects - Wisnu Agung Pramudya; Nurhamdoko Bonifacius; Hery Budiyanto (Proceedings of International Conference of Graduate School on Sustainability, 2026)
Contract Change Orders (CCOs) are a major challenge in construction projects, directly impacting cost, time, and quality. Contract changes can occur at various stages of project implementation and are influenced by a variety of technical and non-technical factors. This study aims to identify the causes, impacts, and control strategies for CCOs by analyzing 30 scientific articles from Google Scholar. The method used was a literature review, selecting relevant journals based on keywords, topic suitability, and completeness of research information. The analysis results indicate that the main causes of CCOs include mismatches between design and field conditions, planning errors, incomplete technical specifications, additional owner-scope of work, and external factors such as weather, material price increases, and policy changes. The impact of CCOs appears significant on cost overruns and time overruns, with some projects experiencing contract value increases of more than 25% and delays of more than 30%. In addition, CCOs also affect productivity, work quality, and the potential for disputes between parties. This study emphasizes the importance of thorough planning, high-quality design documents, inter-stakeholder coordination, and the use of analytical methods in change management as mitigation strategies to minimize the frequency and impact of CCOs. These findings are expected to serve as a reference for academics and practitioners seeking to improve the effectiveness of construction project management.